2003
DOI: 10.3748/wjg.v9.i3.399
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic innervation of human esophageal and cardiac carcinoma

Abstract: AIM:To investigate the distribution of neuropeptideimmunoreactive nerve fibers in esophageal and cardiac carcinoma as well as their relationship with tumor cells so as to explore if there is nerve innervation in esophageal and cardiac carcinoma. METHODS:Esophageal and cardiac carcinoma specimens were collected from surgical operation. One part of them were fixed immediately with 4 % paraformaldehyde and then cut with a cryostat into 40-µm-thick sections to perform immunohistochemical analysis. Antibodies of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Tumours induce innervation around themselves 3 10 and, in general, high levels of innervation in tumours correlate with a poor disease outcome 2 7 . Tumour cells have the ability to produce substances, such as Nerve Growth Factor (NGF), that stimulate the growth and improve the survival of nerve cells 11 12 .…”
Section: Biological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumours induce innervation around themselves 3 10 and, in general, high levels of innervation in tumours correlate with a poor disease outcome 2 7 . Tumour cells have the ability to produce substances, such as Nerve Growth Factor (NGF), that stimulate the growth and improve the survival of nerve cells 11 12 .…”
Section: Biological Backgroundmentioning
confidence: 99%
“…Traditionally, the nervous system has not been considered to be actively involved in the process of metastasis. However, recent studies have demonstrated the presence of neurons in peritumoural regions of several human tumours, and the number of tumour-associated neurons has been correlated with metastases 2 3 . The relative importance of pre-existing versus newly-formed neurons to metastasis is not understood.…”
mentioning
confidence: 99%
“…In addition to the above discussed induction of metastasis formation, the innervation of tumors might support a proinflammatory milieu by the release of the according neurotransmitters. For example, peptidergic nerve fibres have been found in esophageal and cardiac carcinoma [ 43 ]. In that study, substantial amounts of substance P have been found, which is a key mediator of inflammatory processes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the in vitro data, it is, therefore, reasonable to expect an enhanced density of nerve fibers within the tumor. However, while some studies do provide evidence of neurogenesis within the tumor [34, 66, 68, 7274], others report normal or even reduced neuronal density within the tumor foci, and the presence of nerve fibers exclusively around the vasculature or in the peripheral stroma of the tumor [7578]. The challenge in quantifying neuronal fibers by immunohistochemistry and the difficulty of differentiating between autonomic and sensory fibers in tissue may contribute to the discrepancy of reported tumor innervation.…”
Section: Afferent Nervous Systemmentioning
confidence: 99%